LA DESIGUALDAD EN LA CONSTRUCCIÓN DE LA SUBJETIVIDAD PERIODÍSTICA. ANÁLISIS DE LOS BLOGS DE ELPAIS.COM Y ELMUNDO.ES DESDE UN PUNTO DE VISTA DE GÉNERO - Dra. Elena BANDRÉS GOLDÁRAZ,Dra. María GÓMEZ Y PATIÑO,Dra. Carmen MARTA-LAZO, (Fonseca, Journal of Communication, 2023)
We present a quantitative study based on a random strategic selection of blogs sample written by women in two reference newspapers (El Mundo.es & El País.com) in Spain to find out the issues dealt and concerning, women as they enable the construction of women's subjectivity and their social visibility. This agenda-setting analysis visibilizes these female blog whose subject's choice discovers the existing inequality, both in number (women and men writers), as well as selection of the major issues: politics and economy, where women's presence nearly does not exist.